Large range nanopositioning stage design: A three-layer and two-stage platform. (July 2016) - Torralba, M.; Valenzuela, M.; Yagüe-Fabra, J.A.; Albajez, J.A.; Aguilar, J.J.
Abstract: In this article, a novel two-dimensional nanopositioning platform (NanoPla) design is described. Its requirements are not only sub-micrometer accuracy for nanotechnology applications, but also long working range ( XY -motion 50 mm × 50 mm). These features increase the common range operation of devices for nanotechnology issues (e.g. an atomic force microscope), and the number of potential metrological applications: positioning for manufacturing, manipulation or sample characterization. This novel design is characterized by a three-layer architecture and a two-stage motion strategy, which minimizes the measurement error. The manufactured prototype is here justified considering precision engineering principles and a wide state-of-art study of the literature, regarding long range nanopositioning stages. The simulations, the experimental results and the error budget also allowed, first, the optimization and, secondly, the validation of the design at nanometer scale.